Experiences of BSN Students regarding Application of Nursing Theories at Clinical - Arif, Shireen; Nasir, Alia (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To explore the experiences of BSN students regarding application of nursing theories at the clinical practice. METHODOLOGY: Qualitative Phenomenology approach was used by using semi-structured questionnaire. Study was conducted at Ziauddin College of Nursing BSN Year IV Semester VIII students after completion of Nursing Theories course. Data was collected from four in-depth interviews from key informants and 3 Focus Groups having 6 members in each group. Data was collected till saturation occurs. Interviews were tape recorded and notes were also taken. Total 22 nursing students participated after signing consent form. RESULTS: The result of the study revealed challenges at clinical site under that helpless, unavailability of subject expert instructor, lack of clinical faculty interest, delay in assignment submission and no long term application were emerged as the categories of the data. CONCLUSION: The current study highlights the experiences of application of nursing theory while applying it at the clinical area.